Brain-Machine Interface Circuits and Systems - Zjajo, Amir.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a complete overview of significant design challenges in respect to circuit miniaturization and power reduction of the neural recording system, along with circuit topologies, architecture trends, and (post-silicon) circuit optimization algorithms. The introduced novel circuits for signal conditioning, quantization, and classification, as well as system configurations focus on optimized power-per-area performance, from the spatial resolution (i.e. number of channels), feasible wireless data bandwidth and information quality to the delivered power of implantable system.
Introduction -- Neural Signal Conditioning Circuits -- Neural Signal Quantization Circuits -- Neural Signal Classification Circuits -- Brain-Machine Interface: System Optimization -- Conclusions and Recommendations -- Appendix -- Index.
Keywords: Electronic circuits; Biomedical engineering; Biotechnology; Electronic Circuits and Systems; Biomedical Engineering and Bioengineering; Biotechnology